A Study on Impact of Industrial Air Pollution on Agricultural Production: Examining the effect of industrial air pollution on crop yield and economic losses (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This paper intended to concentrate on what industrial air pollution means for crop yield by researching the connection among result and changes in factors. A translog production work was assessed with regards to stochastic outskirts investigation utilizing information gathered from a field review on account of corn. The collaboration between the elements just as the effect of industrial air pollution on the connection between factors was dissected utilizing mathematical recreation, trailed by the assessment of monetary misfortunes of corn yield in the dirtied region. Results show that industrial air pollution causes a decline in crop yield for two reasons. In the first place, industrial air pollution changes the result flexibilities of production factors and lessens its outright sum. Second, industrial air pollution prompts the connection among work and capital, work and synthetics, capital and seeds to change from substitutable to integral it additionally brought about a contrary outcome for the connection among capital and synthetics. The paper presents another clarification of what industrial air pollution means for agricultural production according to a financial point of view.